ANALYSIS OF GIRDER ON OVER HEAD CRANE WITH 4 TON CAPACITY USING INVENTOR - samud, dimas (Universitas Majalengka, 2025)
In the field of overhead crane construction, a girder is a beam that is positioned between two supports that can be pillars or abutments. The shape of the girder beam varies, ranging from square, trapezoidal, letter U, letter I to letter T. The I-girder type is an I-shaped beam made of composite or non-composite materials. This type of girder is most often used in bridge construction in Indonesia. It is natural that all manufacturers must provide and accept custom manufacturing. The research conducted in this report focuses on girders for overhead cranes to withstand a load of 4 tons. The research was conducted by comparing the results of the manual calculation process with the simulation process using Inventor software. . Steel Girder Material ST 37 Standard JIS 3101 SS400 profile I beam size 350 x 175 x 7 x 11 mm.The results obtained are Normal Stress on the beam of Shear Stress 1.96 N / mm2 Deflection that occurs in the I-section beam 1.2 mm. Where E is the modulus of elasticity of Steel of 200,000 Mpa.